Emerging Technologies in the Area of Food Sciences - Gopalan, Natarajan (Defence Life Science Journal, 2017)
In the modern era, world has experienced tremendous boost in the field of food science and technology, realising its impact on the economic growth and people’s standard of living. India is using its newer technology for food processing in the field of science and technology. We are among the world’s top nations in the number of scientific publications and patents in food technology. The government has made considerable investment and is encouraging public-private partnership to achieve self-reliance in different agricultural sectors. It has a strong presence in the field of biotechnology, particularly related to agriculture technology, including pre- and post-harvest management, processing technology etc.